2013
DOI: 10.1016/j.comnet.2012.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Energy efficiency of femtocell deployment in combined wireless/optical access networks

Abstract: Optical/wireless convergence has become of particular interest recently because a combined radio wireless and optical wired network has the potential to provide both mobility and high bandwidth in an efficient way. Recent developments of new radio access technologies such as the Long Term Evolution (LTE) and introduction of femtocell base stations open new perspectives in providing broadband services and applications to everyone and everywhere, but the instantaneous quality of radio channel varies in time, spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…Femtocells are small, low power BS typically design for use in a home or small business. It can significantly boost up wireless network capacity [8] and studies in [9] has shown that the deployment of femtocells can significantly increase both access data rates and energy efficiency in areas with high population densities thus making the femtocell as an attractive solution in order to increase network capacity and coverage in an economical way. Trends have shown that traffic from wireless and mobile devices will surpass traffic from wired devices by year 2018 [10].…”
Section: Integrated Optical-wireless Access Networkmentioning
confidence: 99%
See 4 more Smart Citations
“…Femtocells are small, low power BS typically design for use in a home or small business. It can significantly boost up wireless network capacity [8] and studies in [9] has shown that the deployment of femtocells can significantly increase both access data rates and energy efficiency in areas with high population densities thus making the femtocell as an attractive solution in order to increase network capacity and coverage in an economical way. Trends have shown that traffic from wireless and mobile devices will surpass traffic from wired devices by year 2018 [10].…”
Section: Integrated Optical-wireless Access Networkmentioning
confidence: 99%
“…In [17], the authors have proposed a centralized scheduling mechanism that shortens the packet delay and the time of transmitting data upon requesting bandwidth. Meanwhile, the work on energy efficiency of the integrated access network can be found in [9], [18], [19]. In [18], the authors discussed the energy efficient bandwidth allocation mechanism that adopts an optical burst switching technique for long reach network.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations